P1_4 The Master Chief Revisited - Bosley, Robbie Ross; Hunter, Amelia; Galloway, James Bernard; Michalowska, Jasmine (Physics Special Topics, 2016)
In this paper we expand upon the findings of “P1 1 The Chief”s Downfall” by examining the trend of the velocity with which the Master Chief impacts the ground at the beginning of the videogame ’Halo 3’ with varying initial velocity, using an iterative process, and attempt to find an equation linking the two.